SEKOLAH UNGGUL (KAJIAN KONSEP PENDIDIKAN LEARNING BY DOING DALAM PERSPEKTIF AL-QUR’AN) - Raihan, Nur (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
The conclusion of this research is a Leaning by Doing learning model in the perspective of the Qur'an at Ciganjur School, South Jakarta by using several approaches, namely the experiential approach, the habituation approach to develop students with routine and programmatic habituation. The preparation carried out is to compile the vision, mission and program of Sekolah Alam, compile the implementation of learning, compile lesson schedules and prepare teaching preparation documents. The learning model is implied in learning in schools through an agenda of activities related to the physical and spiritual as well as extracurricular. Another interesting thing found in this researcher is the learning model implemented in the School of Nature, which is a learning integration method that combines kauniyah and kauliyah verses on Earth. So that students are able to grow up to become caliphs on Earth. So that the results can be seen from the perspective of students who show the maturity of interaction with good nature. Students not only master the cognitive aspects, but the psychomotor and effective aspects also show excellent results. The findings of this study are that the learning model of learning by doing perperktif Al Qu'an is carried out in the form of Al-I'tibar, namely taking lessons from nature, thinking, being grateful for favors and exploring the secrets of Allah's creation and Al-Intifa' which is to take advantage and make the best use of it, the three Al-Ishlahs are to improve, preserve nature and maintain it in accordance with the purpose of His creation.